匈奴의 休屠王 태자 金日磾(金日)에 관한 硏究 - 이종호(Lee Jong-Ho) (백산학보, 2010)
Recently the Three Kingdoms Period, Goguryeo and Baekje into one category and Silla and Kaya into the other category are granted by the flood of studies fulfilling. It is no doubt that Onjo King of Baekje was the son of Goguryeo's beginner namely King Gojumong. A recent study of Silla and Kaya on the go is very alarming. The origin of Silla & Kaya may be closely linked with the Xiongnu. The descendant of Prince KimIlJe of King Hyujeo(休屠王) come to the Korean peninsula and become the key in the Silla and Kaya Dynasty. Since the nomadic Xiongnu(Hun) riders are known without a settlement of nomads, so that the ruins and the relics are very pure. Because the letters of Xiongnu are not known, It's very difficult to understand on the past of Xiongnu. However, recent excavations of Xiongnu sites and studies conducted to increasing numbers of information. The athor explained the study on the Kim IlJe known as Kim's ancestor in Silla and Kaya Dynasty, the flow process into the Korean Peninsula. And also explained on the main arena of bloody fight between Xiongnu and China, mainly Haseojurang(河西走廊), the ruins of hyujeoseong(休屠城) and Mt. Eonji(焉支山 or 燕支山). KCI Citation Count: 0